How 6 Organizations Developed Tools and Processes for Social Determinants of Health Screening in Primary Care: An Overview. Issue 1 (January 2018) - LaForge, Kate; Gold, Rachel; Cottrell, Erika; Bunce, Arwen E.; Proser, Michelle; Hollombe, Celine; Dambrun, Katie; Cohen, Deborah J.; Clark, Khaya D.
Abstract : Little is known about how health care organizations are developing tools for identifying/addressing patients' social determinants of health (SDH). We describe the processes recently used by 6 organizations to develop SDH screening tools for ambulatory care and the barriers they faced during those efforts. Common processes included reviewing literature and consulting primary care staff. The organizations prioritized avoiding redundant data collection, integrating SDH screening into existing workflows, and addressing diverse clinic needs. This article provides suggestions for others hoping to develop similar tools/strategies for identifying patients' SDH needs in ambulatory care settings, with recommendations for further research.